Travel experience of Southeast Asian solo female travelers - Nguyen, Dang Thuan An; Hsu, Liwei (Universitas Pendidikan Indonesia, 2022)
AbstractThis study aims to explore travel experience of Southeast Asian solo female travelers. In-depth interviews were conducted with 18 Southeast Asian solo female travelers and analyzed using thematic analysis. The findings show that sociocultural constraints strongly influence Southeast Asian solo female travelers’ travel experiences in terms of subject of gaze, being adjustable, and self-development. This study only represents a particular group of solo female travelers and could focus on one patriarchal society, where these women experience a similar degree of social-cultural constraints. However, travel associations and marketers should provide comprehensive services to address their concerns and target this growing market. This study contributes by addressing the lack of research on travel experiences of Southeast Asian solo female travelers and by providing perspectives through in-depth interviews. AbstrakPenelitian ini bertujuan untuk mengeksplorasi pengalaman perjalanan sendiri wisatawan wanita Asia Tenggara. Wawancara mendalam dilakukan kepada 18 wisatawan wanita Asia Tenggara yang melakukan perjalanan sendiri dan dianalisis menggunakan analisis tematik. Temuan menunjukkan bahwa kendala sosiokultural sangat mempengaruhi pengalaman perjalanan sendiri mereka dalam hal subjek pandangan, penyesuaian diri, dan pengembangan diri. Studi ini hanya mewakili kelompok tertentu dari wisatawan wanita yang melakukan perjalanan sendiri dan dapat fokus pada satu masyarakat patriarki, di mana para wanita ini mengalami tingkat kendala sosial-budaya yang serupa. Namun, asosiasi perjalanan dan pemasar harus memberikan layanan yang komprehensif untuk mengatasi masalah mereka dan menargetkan pasar yang berkembang ini. Studi ini berkontribusi dengan mengatasi kurangnya penelitian tentang pengalaman perjalanan sendiri wisatawan wanita Asia Tenggara dan dengan memberikan perspektif melalui wawancara secara mendalam.